2013
DOI: 10.1121/1.4824629
|View full text |Cite
|
Sign up to set email alerts
|

On the suitability of ISO 16717-1 reference spectra for rating airborne sound insulation

Abstract: A standard proposal for rating airborne sound insulation in buildings [ISO 16717-1 (2012)] defines the reference noise spectra. Since their shapes influence the calculated values of single-number descriptors, reference spectra should approximate well typical noise spectra in buildings. There is, however, very little data in the existing literature on a typical noise spectrum in dwellings. A spectral analysis of common noise sources in dwellings is presented in this paper, as a result of an extensive monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
1
10
0
5
Order By: Relevance
“…The preliminary study, although having a relatively small number of participants (i.e., nine subjects), demonstrated that when using a broadband noise type signal such as pink, white, or grey noise as a test signal compared to a music sound source, the subjectively estimated sound insulation was judged differently. This result confirms previous findings [10,35].…”
Section: Signal Descriptionsupporting
confidence: 83%
See 1 more Smart Citation
“…The preliminary study, although having a relatively small number of participants (i.e., nine subjects), demonstrated that when using a broadband noise type signal such as pink, white, or grey noise as a test signal compared to a music sound source, the subjectively estimated sound insulation was judged differently. This result confirms previous findings [10,35].…”
Section: Signal Descriptionsupporting
confidence: 83%
“…Recently, a replacement for ISO 717-1, designated as ISO 16717-1 [7], has been proposed [8], which includes changes to the frequency range included in the single number ratings [9,10]. However, no evaluation has been introduced into the proposed new standard that classifies hearing sensation.…”
Section: Introductionmentioning
confidence: 99%
“…On this topic, Masovic et al [36] made a study on the suitability of ISO CD 16717-1 [37] reference spectra for rating airborne sound insulation. The ISO CD 16717-1 [37] "living" and "traffic" spectra correspond to the reference spectra C (50-5000 Hz) and C tr (50-5000 Hz) of ISO 717-1 [35], respectively.…”
Section: Single Number Quantities Analysismentioning
confidence: 99%
“…On this topic, Masovic et al [32] made a study on the suitability of ISO CD 16717-1 [25] reference spectra for rating airborne sound insulation. The ISO CD 16717-1 [25] spectra living and traffic correspond to the reference spectra C (50-5000 Hz) and Ctr (50-5000 Hz) of ISO 717-1 [21], respectively.…”
Section: Façade Sound Insulationmentioning
confidence: 99%
“…The ISO CD 16717-1 [25] spectra living and traffic correspond to the reference spectra C (50-5000 Hz) and Ctr (50-5000 Hz) of ISO 717-1 [21], respectively. Masovic et al [32] demonstrated, with an extensive noise monitoring in a number of dwellings recordings of 38 potentially disturbing activities, that the reference spectrum for living noise (Lliving), should be redefined to better match the typical spectrum of noise in dwellings because it seems to be rather high at lower frequencies, especially below 100 Hz. Moreover, in the case of noise generated by sources of music with strong bass content the reference spectrum for traffic noise (Ltraffic) seems to be more appropriate above 100 Hz than Lliving.…”
Section: Façade Sound Insulationmentioning
confidence: 99%